CRITICAL DISCOURSE ANALYSIS OF POLICE OFFICER’S NEGATIVE REPRESENTATION TOWARD #PERCUMALAPORPOLISI ON TWITTER/X: ANALISIS WACANA KRITIS REPRESENTASI NEGATIF APARAT KEPOLISIAN MELALUI TAGAR #PERCUMALAPORPOLISI DI TWITTER/X - Nisrina Dauty; Cece Sobarna; Nani Darmayanti (LLDIKTI Wilayah X, 2024)
Social criticism of the phenomenon happened on social media with popularized hashtags like #percumalaporpolisi on Twitter. Police officer incompetence in a sexual assault case in Luwu Timur, South Sulawesi, triggers citizens to create this hashtag. This research aims to describe the negative representation of Police officers by Indonesian Twitter users through #percumalaporpolisi. The qualitative research method used in this research is Norman Fairclough’s critical discourse analysis theory. Indonesian Police officers explicitly and implicitly represented through words usage, and/or sentences in negative ways. On the other side, Indonesian netizens (Twitter users) have been known for their distrust towards police officers for a long time, tending to use harsh words, posting their disagreement towards something harshly, and becoming the most impolite netizens in southeast Asia. Lastly, Police officers have had several controversial histories, followed by the exposed scandal of sexual harassment in Luwu Timur, explained as a social practice dimension. The negative representations are exposed both explicitly and implicitly through words and sentences. The representations were affected by how netizens interacted on social media perceiving police officers and the behavior of the netizens. It was getting worse as scandals in the police institutions were also supported by police impunity.